Ensalades en clausura: Una primera aproximació als cançoners del convent de les carmelites descalces de Santa Teresa de Vic. - PESSARRODONA, AURÈLIA (Scripta, 2016)
The recent finding of two songbooks in the convent of Saint Therese in Vic (Barcelona), dated to the 17th century, broadens and enriches strikingly what was already known about the literary creation in monasteries and performative manifestations --music, theater, dance--in the enclosed life of female discalced Carmel during the Modern Age. This article provides a first approach to these songbooks, that shows significant differences between them. The first one collects a foreign and older repertory, from 16th and early 17th centuries, that includes the unusual presence of ensaladas edited by Mateu Fletxa the Youger in 1581. The other one is an excellent example of literary creation of the nuns, with works dated from 17th to early 18th century. As well as a description of the manuscripts, an approximation to their content and placing them in their context, the article includes some reflections concerning the performative practice of this repertory, above all of the ensaladas.